4(4x-6)=2(8x+1)

Simple and best practice solution for 4(4x-6)=2(8x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(4x-6)=2(8x+1) equation:


Simplifying
4(4x + -6) = 2(8x + 1)

Reorder the terms:
4(-6 + 4x) = 2(8x + 1)
(-6 * 4 + 4x * 4) = 2(8x + 1)
(-24 + 16x) = 2(8x + 1)

Reorder the terms:
-24 + 16x = 2(1 + 8x)
-24 + 16x = (1 * 2 + 8x * 2)
-24 + 16x = (2 + 16x)

Add '-16x' to each side of the equation.
-24 + 16x + -16x = 2 + 16x + -16x

Combine like terms: 16x + -16x = 0
-24 + 0 = 2 + 16x + -16x
-24 = 2 + 16x + -16x

Combine like terms: 16x + -16x = 0
-24 = 2 + 0
-24 = 2

Solving
-24 = 2

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| m+-84=-126 | | 69=x+1/2(x-6) | | -86-72=m | | -31*m=434 | | 4x-15=-3x+15 | | (8x+18)+(6x+4)+90=180 | | -4+-81=n | | 363/-11=j | | -15*-32=z | | x^4+8x^3+3x^2+24x=0 | | -98-3=v | | 8a-56a= | | 17.5+1.5y=-y | | -19+-20=w | | 15x^2-10x-30=0 | | 4x*x=82 | | G*-11=627 | | 675/-25=c | | x*2+4x=9 | | -14+-58=c | | 2x+7=2(x+2) | | 2x-3y=-35 | | x^3-15x^2+3x-14=0 | | -97-r=-76 | | R=80x+12 | | x^3-15x^2-3x-14=0 | | -20*-35=n | | 7x^2+26x-8=0 | | x^2+16=x^2+12x | | -20x-35=n | | 3*x+5=17 | | 4x+2x-10=6+x |

Equations solver categories